2021
DOI: 10.1039/d1ra03082e
|View full text |Cite
|
Sign up to set email alerts
|

A sandwich SERS immunoassay platform based on a single-layer Au–Ag nanobox array substrate for simultaneous detection of SCCA and survivin in serum of patients with cervical lesions

Abstract: A novel SERS immunoassay platform for simultaneous detection of SCCA and survivin based on Au–Ag nanoshells (Au–AgNSs) combined with a single-layer Au–AgNB array substrate was proposed in the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Liu et al fabricated a SERSbased immunoassay to simultaneously detect squamous cell carcinoma antigen (SCCA) and survivin (Figure 13b). 261 In their unique design, the detection substrate consisted of gold− silver nanoshells (Au−Ag NSs) with DTNB and 4-amino thiophenol (4-ATP) as the Raman reporters, and monoclonal anti-SCCA and antisurvivin antibodies for targeting the respective antigen. The capture substrate consisted of a gold− silver nano box (Au-AgNB) array coated with polyclonal antibodies.…”
Section: Sers-based High Throughput Proteomic Assays For Ex Vivo Diag...mentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al fabricated a SERSbased immunoassay to simultaneously detect squamous cell carcinoma antigen (SCCA) and survivin (Figure 13b). 261 In their unique design, the detection substrate consisted of gold− silver nanoshells (Au−Ag NSs) with DTNB and 4-amino thiophenol (4-ATP) as the Raman reporters, and monoclonal anti-SCCA and antisurvivin antibodies for targeting the respective antigen. The capture substrate consisted of a gold− silver nano box (Au-AgNB) array coated with polyclonal antibodies.…”
Section: Sers-based High Throughput Proteomic Assays For Ex Vivo Diag...mentioning
confidence: 99%
“…SERS-based immunoassays have also been developed with bimetallic NPs for detecting multiple tumor antigen markers. Liu et al fabricated a SERS-based immunoassay to simultaneously detect squamous cell carcinoma antigen (SCCA) and survivin (Figure b) . In their unique design, the detection substrate consisted of gold–silver nanoshells (Au–Ag NSs) with DTNB and 4-amino thiophenol (4-ATP) as the Raman reporters, and monoclonal anti-SCCA and antisurvivin antibodies for targeting the respective antigen.…”
Section: Labeled Surface-enhanced Raman Nanoprobes For Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As HPV vaccination does not protect against all high-risk HPV types [ 77 , 78 ], more work on multivariant HPV vaccines could help in this area. However, excellent quality screening programmes are still crucial in preventing cervical cancer in this new HPV vaccination era [ 79 , 80 , 81 , 82 ].…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Several studies have shown the potential of this technique for cervical precancer and cancer diagnosis based on changes to the biochemistry of cervical tissues and cells [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In addition, both Raman spectroscopy [ 18 , 19 , 20 ] and surface-enhanced Raman spectroscopy (SERS) using gold or silver nanoparticles [ 21 , 22 , 23 , 24 ] have shown good potential for cervical cancer detection using blood serum or plasma. Apart from studies on pellets of exfoliated cells [ 25 , 26 ] and our own studies on single exfoliated cells [ 13 , 15 , 17 , 27 , 28 , 29 ], there have been relatively few cytology studies using Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%